Método de avaliação do emprego das práticas lean: uma aplicação em indústrias moveleiras do sudoeste do Paraná - Cenci, Vanessa Rebeca (2021)
Many companies seek to remain competitive in an increasingly competitive market, in which customers are more demanding. The use of Lean practices is an important mechanism to obtain better performance rates in organizations. However, small companies have difficulties in introducing changes, adding concepts, and accepting transformation in order to remain competitive. In this scenario, some factors may be the cause of barriers to the implementation and use of Lean practices, one of them being the lack of knowledge. The objective of this study is to develop a method to evaluate the use of Lean practices. The model developed was applied in furniture industries in the southwest of Paraná, which have several industrial management systems, as well as productive divergences. The method was applied to validate and identify possible inconsistencies. The Proknow-C tool was used to select the bibliographic portfolio and survey the main authors, articles and periodicals according to the theme addressed, thus identifying the main practices described in the works and that were adopted as reference to evaluate their use on the factory floor. In the sequence, the STP (Toyota Production System) house structure was used and the most cited practices in the selected articles were distributed in the base elements, JIT, people, and quality. A scoring system was created and criteria and weights were assigned to quantify the use of Lean practices. The evaluation instrument contains an interview script composed of 87 questions, adapted from authors in the literature, to identify the level of Lean usage in the production environment. The SAE J4000 and J4001 norms were used, which make available a list with attribution of values for evaluation items, which was adapted for this research. The answers from the interview application were obtained through different data sources, such as: people, process observation, and documents. The method was applied in 6 companies in the Southwest of Paraná, named company A, B, C, D, E and F, being medium and large companies, for presenting relevance to the study. With the result of the application of the evaluation instrument it was identified that the total average percentage of Lean employment of all the companies was 33.46%. Factors such as the lack of knowledge of the practices, the high cost of implementation and the lack of qualified employees were the main obstacles encountered. The study revealed that the medium-sized companies are the ones that employ Lean the most when compared to the large-sized company. Finally, the analysis of the results identified opportunities for improvement in relation to the use of the practices in all companies.